SIKAP AL-QUR’AN TERHADAP YAHUDI: (Jawaban Atas Tuduhan Terhadap Al-Qur’an Anti-Semitis) - Amin , Muhammad Maghfur (QOF, 2020)
This paper is a response to an issue exhaled by Ariel Muzicant about al-Qur'an anti-Semitic accusations. The issue is the writing of the Vice President of the European Jewish Congress, Ariel Muzicant, which is contained in a recent paper entitled "An End to Antisemitism! A Catalog of Policies to Combat Antisemitis ". They revealed that the Qur'an and the Gospels had to be reexamined, at the point which contained anti-Semitic doctrine. Islamic and Christian documents that discriminate against Jews must be eliminated and removed. This paper tried to answer the above accusation, by pointing out verses related to this theme.This paper is a library research using thematic methods. From this research it was found that; (1) The attitude of the Qur'an towards the Jews cannot be fully seen as anti-Semitic attitude; (2) Some verses which have the potential to create an impression of cynicism towards Jews, should be returned to the universal message of the egalitarian Qur'an. (3) The verses that seem anti-Semitic are derived by the formation of a logical historical context, namely as a form of response to the attitude of the Jews